A new method for assessing the trophic state of large dams in Cyprus using satellite remotely sensed data - Toulios, Leonidas; Clayton, Chris R I; Hadjimitsis, Diofantos G. (My University, 2010)
A timely low-cost method providing information on water quality and trophic state to various users of reservoir or dam water is a must. Conventional methods involved tedious and expensive in situ and laboratory studies. Satellite-borne sensors have the capability of providing repetitive, low-cost, multispectra, timely and reliable information over areas. This paper shows the development of a new method for assessing the trophic state in inland water bodies such as dams. The method is based on matching the atmospheric corrected reflectance values obtained from Landsat-5 Thematic Mapper (TM) image data with the defined spectral signature ranges obtained from ground spectro-radiometric measurements in order to assess the trophic state conditions. The proposed method has been applied to Landsat TM and Enhanced Thematic Mapper (ETM) satellite images of the Kourris and Asprokremmos Dams in Cyprus, acquired during the winter, spring, summer and autumn period. The reflectance values for the images acquired on 3 June 1985, 11 September 1998, 11 May 2000 and 31 January 2001 for the Asprokremmos Dam were found to be 4.5, 3.5, 3.7 and 11.2%, and those for the Kourris Dam were found to be 5, 3.5, 3.1 and 5.2%, respectively. Reflectance values between 3 and 7% correspond to a eutrophic state and values >7% to a hypertrophic state. The results obtained from the proposed method were found to comply with those found using the trophic state index (TSI) approach. For example, the trophic state for the Landsat TM images of Asprokremmos Dam acquired on 11 May 2000 and 31 January 2001, was determined to be TSI=68 and 79, respectively, using the available secchi disc depths (SDDs) and the Carlson TSI. Such values correspond to eutrophic and hypetrophic trophic states that comply with the same outcomes found from the proposed method.
Keywords: Water quality; Trophic state; Spectro-radiometer; Remote sensing; Landsat Thematic Mapper; Eutrophic; Dam